Sexually Transmitted Diseases A Practical Guide for Primary Care - Skolnik, Neil S.; Clouse, Amy Lynn.; Woodward, Jo Ann.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana Press, 2013)
Sexually Transmitted Diseases: A Practical Guide for Primary Care, Second Edition, covers the diagnosis and treatment of STDs and other information critical to patient care, and reflects the last five years of significant changes in information about STDs. Updated to reflect the 2010 Centers for Disease Control Guidelines on the Treatment of STDs, this book also contains new information about: -the epidemiology of herpes virus infections -expedited partner therapy -changes in recommendations for HPV vaccination for men -changes in resistance patterns for antimicrobial therapy for gonorrhea and chlamydia -treatment recommendations for genital warts In order to better meet clinician needs, the book has been streamlined to quickly convey critical, evidence-based information. Whether seeking information about particular conditions (including HPV, herpes, syphilis, trichomaniasis, HIV, and others) or related patient issues (such as STD exposure evaluation and evaluation of sexual assault), Sexually Transmitted Diseases, Second Edition, contains all the knowledge clinicians need in a friendly, to-the-point format.
Human papillomavirus and genital warts -- Genital herpes -- Chlamydia -- Gonorrhea -- Pelvic inflammatory disease -- Viral hepatitis -- HIV: identification, diagnosis and prevention -- Syphilis -- Trichomoniasis -- Lymphogranuloma venerum, chanchroid, granuloma inguinale, and molluscum contagiosum -- Ectoparasites: scabies and pediculosis pubis -- Public health and prevention -- Evaluation and treatment of STD exposure and sexual assault.
Keywords: Medicine; Gynecology; Obstetrics; Emerging infectious diseases; Emergency medicine; Medicine & Public Health; Primary Care Medicine; Infectious Diseases; Gynecology; Obstetrics/Perinatology.